Fundamental motor skill proficiency is necessary for children's motor activity inclusion - Barela, José Angelo [UNESP] (FapUNIFESP (SciELO), 2013)
Motor development is influenced by many factors such as practice and appropriate instruction, provided by teachers, even in preschool and elementary school. The goal of this paper was to discuss the misconception that maturation underlies children's motor skill development and to show that physical education, even in early years of our school system, is critical to promote proficiency and enrolment of children's in later motor activities. Motor skill development, as a curricular focus, has been marginalized in many of our physical education proposal and in doing so, we have not promote motor competence in our children who lack proficiency to engage and to participate in later motor activities such as sport-related or recreational.
Keywords: Fundamental motor skills; Motor development; Physical education; Skillfulness